Ants (Hymenoptera: Formicidae) of Durango, México - Soto-Cárdenas, Miguel Angel; Vásquez-Bolaños, Miguel; Gutiérrez-García, Cipriano; Correa-Ramírez, Miguel Mauricio; Torres-Ricario, René; González-Güereca, Martha Celina; Chairez-Hernández, Isaias (Revista Colombiana de Entomología, 2019)
Ants are eusocial insects of wide functional and taxonomic diversity, with worldwide distribution in various terrestrial ecosystems (some introduced by man), with the exception of the poles and in the high mountain peaks. About 15,947 species have been described. In Mexico, 973 are known within 94 genera, and for the state of Durango 60 species are registered within 25 genera. However, the Formicidae knowledge in Durango State is limited as it has received little attention; this is mainly due to the lack of specialists, as well as the territorial extension of it. In order to know the myrmecofauna of the state of Durango, collections were made every 15 days between August 1, 2016 and August 1, 2017, in 56 sites in 19 municipalities located in different ecoregions of the State. Forty (40) species belonging to 24 genera were collected; the Myrmicinae subfamily was the most diverse with 21 species, followed by Formicinae (12 spp.), Dolichoderinae (5 spp.) and Dorylinae and Ponerinae with one species each. Ten (10) more ant species are registered for the state of Durango, the richness increasing from 60 to 70 species and from 25 to 32 genera. This study represents the first effort to know the myrmecofauna of the state of Durango, Mexico.